THE INFLUENCE OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, AND WORK ENVIRONMENT TO EMPLOYEE PERFORMANCE IN PT NIPPON INDOSARI CORPINDO, TBK (SARI ROTI) MM2100 CIBITUNG - Rulianti, Erina (STIE Kusuma Negara, 2019)
Competition in the business world today is increasingly competitive, therefore every company must be able to manage all its human resources effectively and efficiently in order to survive and develop. Human resources that perform well will facilitate the organization to achieve its vision, mission and goals. Without human resources with good performance, it will be difficult for an organization to achieve its stated goals. To improve good human resources one of them is to pay attention to organizational factors, where the organizational factor itself consists of leadership, organizational culture, work environment, and the performance of company employees. This study aims to explain the influence of independent variables, namely leadership style, organizational culture, and work environment with the dependent variable, namely employee performance at PT Nippon Indosari Corpindo, Tbk (Sari Roti) MM2100, Cibitung. This research uses a quantitative descriptive approach which includes descriptive analysis, validity test, reliability test, simple linear regression test, t test, and R2 test supported by the SPSS 22 program. The population used in this study were 79 people who are employees of PT Nippon Indosari Corpindo, Tbk (Sari Roti) MM2100, Cibitung